THE REFLECTION OF PANTHEISM’S PRINCIPLES OF IBN ARAB IN AHMED KHANI'S WORKS" - Ramadhan, Waheed; Hassan, Shvan (Humanities Journal of University of Zakho, 2025)
The concept of pantheism is among the most profound and influential intellectual theories in Islamic mysticism, particularly within Sufism. The idea of pantheism, which reached its pinnacle in the works of the Andalusian Mystic Ibn Arab (1164–1240 CE), the purpose of pantheism: it posits that God manifests within all aspects of existence, and humanity reflects this divine essence. Within this framework, spiritual unity with God is achieved through the annihilation of the self in the divine presence (fana). This study investigates the influence of Ibn Arabi’s pantheism on the Kurdish poet Ahmadi Khani/ Ehmedê Xanî (1651–1707) and explores how this Sufi philosophy is interwoven into his poetry, particularly in his seminal works. To date, no research has specifically examined Khani's engagement with this mystical concept. The findings reveal that Ahmadi Khani embraced Ibn Arabi’s ideas, integrating them into his poetry through a thematic journey from worldly love to divine love. This progression mirrors the Sufi path, wherein metaphorical love (ishq majazi) serves as a bridge to the ultimate truth of divine love (ishq haqiqi). Khani portrays God as the central and absolute existence, with all other beings reflecting this divine light. His poetic vision depicts God as the source of all existence, illuminating creation, which derives its essence and gifts from this divine radiance.